PENGARUH KOMPENSASI, DAN MOTIVASI TERHADAP KINERJA DOSEN DAN KARYAWAN STIE-STMIK MURA LUBUKLINGGAU - Nurhab, Badaruddin (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2018)
This study aimed to investigate the effect of compensation and motivation on the performance of faculty and staff STIE-STMIK MURA Lubuklinggau research uses quantitative methods melaului nalisisi analisisi descriptive view of the help lines sofwe SPSS 18, the respondents in this study amounted to 100 men, results showed that compensation has a relationship strong, positive and significant impact on the value of the variable Motivation 0:46 hubungaan Compensation has a strong, positive and significant impact on the performance of lecturers with a value of 0.25. sedangakan hubungaan Motivation has a strong, positive and significant impact on performance value of 0.56